Relationship Between The Implementation of the Implementation of Occupational Health and Safety And The Determination of The Type Of Siak Hospital In 2025 - Diego, Diego Andika; Edigan, firman; Wahyudi, Arief (Jurnal Olahraga dan Kesehatan (ORKES), 2025)
Siak Hospital as a public health service institution faces challenges in improving the quality of services through the determination of hospital types. The implementation of SMK3 is an important factor that affects the determination of the type of hospital, especially through management commitment, availability of resources, K3 culture, and facilities and infrastructure. This study aims to analyze the relationship between management commitment, resources, K3 culture, and infrastructure facilities to determine the type of Siak Hospital. The research design used quantitative analytics with a cross-sectional approach with 89 respondents selected by stratified random sampling. Analyzed using the Chi-square test. The results showed that there was a significant relationship between management commitment (p=0.003; POR=9.484), resources (p=0.009; POR=5.531), K3 culture (p=0.019; POR=5.253), and infrastructure facilities (p=0.039; POR=4,267) with the determination of the type of hospital. These four factors are significantly related to the determination of the type of Siak Hospital. It is recommended that hospitals strengthen management commitments, ensure adequate resources, and build a positive K3 culture through continuous training and the provision of adequate infrastructure to support hospital type improvement.